Transformational Leadership as an Organizational Mechanism for Creating Innovative Learning Environments: A Qualitative Case Study in Primary Education - Sau, Tenri; Murniati, Murniati; Ilyas, Ilyas; Qadar, Jamal; Nasir, Nasir; Fatmawati, Titi (Journal of Leadership, Management and Policy in Education, 2026)
Creating innovative learning environments has become a strategic priority for schools in responding to digital transformation and the growing demand for twenty-first-century competencies. While transformational leadership has been widely associated with school improvement, little is known about the organizational mechanisms through which it fosters sustainable educational innovation. This study explored how a principal implemented transformational leadership to create an innovative learning environment in a public primary school. A qualitative case study was conducted involving seven purposively selected participants, including the principal, teachers, students, a school committee representative, and an administrative staff member. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using Reflexive Thematic Analysis. The findings revealed that idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration operated as an integrated leadership system that built organizational trust, promoted a shared vision, strengthened collaborative professional learning, and enhanced continuous pedagogical innovation. The study proposes an Integrated Transformational Leadership Mechanismdemonstrating that innovative learning environments emerge through the interaction of trust, collaboration, professional growth, and stakeholder engagement rather than isolated leadership practices. These findings extend transformational leadership theory by explaining the organizational processes underlying sustainable educational innovation and provide practical guidance for strengthening school leadership in primary education.